Goal-oriented Pattern Family Framework for Business Process Modeling - Ahmadi Behnam, Saeed (Université d'Ottawa / University of Ottawa, 2012)
While several approaches exist for modeling goals and business processes in organizations, the relationships between these two views are often not well defined. This inhibits the effective reuse of available knowledge in models. This thesis aims to address this issue through the introduction of a Goal-oriented Pattern Family (GoPF) framework that helps constructing business process models from organization goals while expanding these goals, establishing traceability relationships between the goal and process views, and improving reusability. Methods for extracting domain knowledge as patterns, which are composed of goal model building blocks, process model building blocks, and their relationships, and for maintaining the patterns over time are also presented. The GoPF framework provides the infrastructure for defining pattern families, i.e., collections of related patterns for particular domains. The foundation of GoPF is formalized as a profile of the User Requirements Notation, a standard modeling language that supports goals, scenarios, and links between them. A method for the use of GoPF is defined and then illustrated through a case study that targets the improvement of patient safety in healthcare organizations. The framework and the extraction/maintenance methods are also validated against another case study involving aviation security in a regulatory environment. The GoPF framework is expected to have a positive impact on the scientific community through the formalization, evolution, and reuse of patterns in domain-specific business domains. From an industrial viewpoint, this framework will also help intermediary organizations (such as consulting firms) who are required to repeatedly create and document goal and process models for other organizations in their business domain.
Keywords: goal model; business process model; pattern; pattern family; requirements engineering; knowledge reusability; goal oriented pattern; family framework; CoPF